PERENCANAAN STRATEGIS KEPALA SEKOLAH DALAM PENINGKATAN MUTU: STUDI KASUS SDIT FUTURE ISLAMIC SCHOOL PEKANBARU - Yundri Akhyar; wirda Ningsih (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study aims to elucidate how principals can enhance the quality of education at SDIT Future Islamic School Pekanbaru via strategic planning. This study employs a qualitative approach to elucidate the behaviors of informants in the context of educational planning aimed at enhancing the quality of education. Data was collected through interviews, documentation, and observations. This study recommends obtaining data from the principal, vice principal, and teachers as the primary sources. The search commenced with snowball sampling initiated by the principal, subsequently followed by the teacher responsible for instructing the students. Secondary data sources were derived from field-collected information, including notes and documents pertinent to the study; this phenomenon is referred to as data saturation, indicating that the data exhibits uniformity. The data collection process, specifically reduction, presentation, and conclusion drawing, was conducted concurrently with data analysis in this study. The study's findings reveal that the principal employs several strategies to enhance educational quality at SDIT Future Islamic School, including: (1) Establishing a clear and measurable Vision, Mission, and Objectives, (2) Developing a curriculum aligned with Islamic educational principles encompassing academic, religious, and character dimensions, (3) Training and Developing Educators, (4) Enhancing facilities and infrastructure, (5) Implementing Continuous Monitoring and Evaluation, (6) Fostering Partnerships with Parents and the Community, and (7) Advancing Academic and Non-Academic Achievements.